A history of East Asia from the origins of civilization to the twenty-first century - Holcombe, Charles 1956- (Cambridge University Press, 2011)
"The interconnections among three distinct, yet related societies are at the heart of this book, which traces the story of East Asia from the dawn of history to the present." -- Provided by publisher